(untitled) (Journal of International Studies, 2016)
Since independence in the late 1950s, and in the early 1960s, regional integration in Africa has been identified as an important strategy for the acceleration of development in the continent. The reality of the Post-Cold War international economic world order also stimulates the intensification and fine-tuning of existing regional arrangements leading to the establishment of a supra-national organization and capacity building institutions to address the problems of underdevelopment in Africa. As a consequence, numerous integration groupings have been reorganized and created but their achievements have largely been modest due to inappropriate integration approaches. It is against this background that this article examines the interlocking nexus between regional integration and development in Africa, and maintains that Africans need to adjust their orientation as well as take a major shift towards economic complementarity among member states of integration blocs for the actualization of laudable development. It concludes that inward looking and the involvement of all Africans in the regional integration processes would be the best approach for regional integration to foster development.